Mechanical Performance of Carbon Fiber/Polyamide 6: Comparative Study Between Conditioning in Distilled Water with Heating and Saline Solution - Montagnaa, Larissa Stieven; de Melo Morgado, Guilherme Ferreira; de Paula Santos, Luis Felipe [UNESP]; Guimarães, Alessandro; Passador, Fabio Roberto; Rezende, Mirabel Cerqueira (FapUNIFESP (SciELO), 2024)
It is particularly important to investigate the mechanical performance of carbon fiber (CF) reinforced polyamide 6 (PA6) composites used for automotive and aerospace applications, where diffused moisture of the environment may potentially weaken the material over time. In this work, CF/PA6 composites were subjected to two different types of conditioning: distilled water at a temperature of 80 ºC and saline solution for 12 weeks. The volumetric fraction of CF, PA6 matrix, and the voids of the CF/PA6 composites were determined by acid digestion analysis. At the end of the environmental conditionings, the moisture absorption content and the diffusion coefficient (D) were determined. The mechanical performance of CF/PA6 composites unconditioned and conditioned was evaluated through tensile and interlaminar shear strength (ILSS) tests, and morphological characteristics of the fracture surface after the mechanical tensile test. CF/PA6 composites conditioned in saline solution showed a decrease of 53% (tensile sample) and 72% (ILSS sample) in the diffusion coefficient (D) and insignificant losses of mechanical properties when compared to CF/PA6 composites conditioned in distilled water at 80 ºC. This behavior is attributed to the salt molecules blocking the pores and consequently reducing the migration of water into the samples, maintaining the internal integrity of the specimens.
Keywords: CarbonFiber; Composites; Mechanicalproperties; Moisture; Polyamide 6; Saline environmental